Strategic Framework for Inclusion of Persons with Disabilities in Online (Platform) Work (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
The COVID-19 crisis has accelerated digital transformation and expanded the usage of advanced ICT solutions globally. Moreover, the expansion of remote work platforms and the tendency of modern businesses to outsource part of their business operations to individuals in remote locations creates significant potential for finding employment. According to available data sources, it is estimated that about 700,000 persons in Serbia face some form of disability. Of that number, only about 13% are employed. As a consequence of facing discrimination, persons with disabilities have a greater tendency towards long-term unemployment and complete withdrawal from the labor market. The Internet and advanced digital technologies provide equal opportunities for persons with disabilities to get involved in the digital labor market and increase their chances to find employment and generate income. This paper aims to discuss the potential of digital labor platforms for lowering the long-term unemployment of persons with disabilities in Serbia. Accordingly, the paper provides data on the level of digital competencies of persons with disabilities, since they are fundamental for obtaining employment on digital labor platforms. For that purpose, the standard desk-research method and secondary data analysis of relevant literature, strategic documents and public policies have been performed. The research results provide a deeper insight into the current level of digital competencies of persons with disabilities and suggest a potential solution for improving their chances of obtaining employment and generating income.